Role of supplier evaluation criteria in risk mitigation related to purchasing process - Urbaniak Maciej (Engineering Management in Production and Services, 2021)
The article aims to present the role of supplier evaluation criteria in reducing purchasing risk. Before a purchasing enterprise starts cooperating with suppliers, it set specific requirements and expectations. The fulfilment of these requirements and expectations is verified through the evaluation of suppliers. Evaluation results should indicate potential risks that may arise in the development of partnership cooperation. The article includes the results of empirical research conducted using the computer-assisted telephone interviewing (CATI) technique in medium and large manufacturing companies operating in Poland. The results of the conducted empirical research indicate that companies wishing to partner with suppliers try to limit the level of risk associated with purchases. When evaluating suppliers, manufacturers focus mainly on reducing the risk associated with the defective technical quality of products, timely deliveries, delivery flexibility, time to restore continuity of deliveries, completeness of order fulfilment and delivery documentation, as well as price competitiveness. Also, in the evaluation of suppliers, companies operating in Poland are beginning to pay attention to the reduction of negative environmental impact.